PERBANDINGAN BUDAYA ORGANISASI BANK OCBC NISP SEBELUM DAN SESUDAH MENGALAMI AKUSISI - Steffie Setiadi (Jurnal Administrasi Bisnis, 2018)
This research shows about organizational culture in the company. That it is known that each company has its own organizational culture, which includes beliefs, norms, and shared values that are characteristic of achieving common goals. But the organizational culture in the company can be changed, one of the factors is the acquisition that occurred within the company. Where this study produces a comparative analysis of organizational culture when NISP Bank has not yet been acquired and after acquisition became OCBC NISP Bank. With this comparative analysis, it can be seen the cultural shift that occurs within the company and the expectations of the culture desired by company employees, which aims to be able to get a suitable cultural picture so that it can increase the employee loyalty, productivity and movement towards for corporate goals. Keywords: Organizational culture, Acquisition, Strategy